Quantum molecular dynamics of guest molecules in supramolecular complexes - Panesar, Kuldeep Singh (2009)
The quantum motion of guest molecules has been studied in a variety of calixarene host-guest complexes, and in a endohedral fullerene complex. The guest molecules of the calixarene complexes studied each comprise weakly hindered methyl groups, which undergo rotation via quantum tunnelling, even at cryogenic temperatures. The rotational motion of the guest methyl-groups has been studied by making temperature and frequency-dependent measurements of proton T1, using field-cycling NMR, thus revealing the spectral density functions of the magnetic dipole-dipole interaction. Crystallographically inequivalent methyl-group environments have been identified and characterised in p-tert-butylcalix[4]arene(1:1)toluene, p-tert-butylcalix[4]arene(1:1)gamma-picoline and p-isopropylcalix[4]arene(2:1)p-xylene. In many of the calixarene complexes the proton spin-lattice relaxation has been observed to be strongly dependent on the thermal history of the sample. Temperature-dependent measurements of proton T1 in samples of p-tert-butylcalix[4]arene(1:1)toluene with partially deuterated guest molecules reveal a systematic reduction in T1 at low temperatures with increased degree of deuteration. Calixarene and fullerene host-guest complexes have been identified as having a potential application in cryogenic MAS-NMR as cryorelaxor complexes, capable of being attached to a large biomolecule and encouraging proton spin-lattice relaxation. The suitability of the calixarene complexes for use in this capacity has been investigated by measuring the temperature-dependence of proton T1 at low temperatures. The quantised rotational and translational motion of dihydrogen confined within an open-cage fullerene—namely, aza-thio-open-cage-fullerene (ATOCF)—has been revealed by inelastic neutron scattering (INS) measurements. The splitting of excited rotational and translational states, due to the low symmetry of the ellipsoidal fullerene cavity, has been directly measured. Assignment of the peaks observed in the INS spectrum has been aided by analysis of the Q-dependence of excitation bands. The thermodynamics of ortho- and parahydryogen have been investigated via temperature dependence measurements. INS measurements have allowed the anistropic rotational potential experienced by the H2 rotor to be determined.